A comparative analysis of derivative regulation following the global financial crisis : an emerging markets perspective - Mpala, Nqobile Natasha (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2015)
The international financial environment has become riskier due to the recent developments in product offerings and failure of regulation to keep abreast with these changes. The Global Financial Crisis exposed inadequacies of regulation, thus consensus on the need for comprehensive and uniform regulation was made by G-20 member states. Imposing exchange trading, clearing, reporting and capital requirements on the derivatives market are some of the ways of dealing with the problems caused by lax regulatory oversight. In this study, through the comparative analysis of derivatives regulation in South Africa, Brazil, India and Turkey, it was established that emerging countries are taking active steps to implement the G-20 agreement. Uniformity in the core rules was noted, with differences in the supportive legislation. Country specific rules which support the macroeconomic factors that are faced by these countries and the infrastructure available for regulatory execution are used amongst countries. The study concluded that current regulation in emerging countries is accommodative and regulatory differences are in line with economic factors in each country.
Keywords: Derivative securities; Global Financial Crisis, 2008-2009; Capital market -- Developing countries; Derivative securities -- Developing countries; International economic relations